2020
DOI: 10.1039/c9se01068h
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-fed photoelectrolysis of water at 0.3 V using gas-diffusion photoanodes of SrTiO3 layers

Abstract: A proton exchange membrane (PEM) system using a SrTiO3 gas-diffusion photoanode achieves vapor-fed photoelectrolysis of water at an applied voltage of 0.3 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…In the PEM-PEC system, we have reported that the coating of Nafion ionomer thin layers is critical for the PEC performance of the macroporous photoanodes such as TiO 2 and SrTiO 3 in the gaseous environment without an aqueous electrolyte. [8][9][10]12 Figure 8a shows the effect of Nafion ionomer treatment on the cyclic voltammetry curves of Ti/WO 3 /Mo-BiV in the vapor-fed water-splitting reaction. In the absence of the Nafion ionomer coating, Ti/WO 3 /Mo-BiV exhibited poor photoresponse in the completely gaseous condition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the PEM-PEC system, we have reported that the coating of Nafion ionomer thin layers is critical for the PEC performance of the macroporous photoanodes such as TiO 2 and SrTiO 3 in the gaseous environment without an aqueous electrolyte. [8][9][10]12 Figure 8a shows the effect of Nafion ionomer treatment on the cyclic voltammetry curves of Ti/WO 3 /Mo-BiV in the vapor-fed water-splitting reaction. In the absence of the Nafion ionomer coating, Ti/WO 3 /Mo-BiV exhibited poor photoresponse in the completely gaseous condition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The other role of the ionomer layer is absorbing water molecules from the gas phase to enhance the hydration of the electrode surface. 11,12 For this reason, the presence of the Nafion ionomer coating promotes photoelectrolysis of water supplied from the gas phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work demonstrates the importance of morphology control in ternary lms, and that higher performance can be achieved by selecting appropriate materials to yield an ideal ternary photoactive layer morphology. 37…”
Section: Sustainablementioning
confidence: 99%